TINJAUAN ASUPAN GIZI DAN KONDISI FISIK PEMAIN SEPAKBOLA TIGO JANGKO FOOTBALL CLUB (FC) KECAMATAN LINTAU BUO KABUPATEN TANAH DATAR - Muhammad Arif; Hastria Effendi; Arif Fadhli Mukhlis (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The problem in this study was that there was still a lack of nutritional intake and the low physical condition of football players Tigo Jangko FC in Lintau District Buo Tanah Datar District. This study aims to determine the nutritional intake and physical condition of football players Tigo Jangko FC District Lintau Buo Tanah Datar District. This research is a descriptive type of research. The results of this research were all 25 Tigo Jangko FC soccer players. Samples were taken by means of